2016
DOI: 10.7567/jjap.55.110305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chirp of pump pulses on broadband terahertz pulse spectra generated by optical rectification

Abstract: The effects of the chirp of the pump pulse in broadband terahertz (THz) pulse generation by optical rectification (OR) in GaP were systematically investigated. It was found that the pre-compensation for the dispersion of GaP is important for obtaining smooth and single-peaked THz spectra as well as high power-conversion efficiency. It was also found that an excessive amount of chirp leads to distortions in THz spectra, which can be quantitatively analyzed by using a simple model. Our results highlight the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In our analysis, we also found that THz spectra can be distorted by the onset of the spectral dip structures around ω/ω p ≈ 1.36 due to destructive interference of chirped laser pulses (inset figure 2) similar to Hamazaki et al [15]. Here, we neglected the effect of collisions in the current scheme.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our analysis, we also found that THz spectra can be distorted by the onset of the spectral dip structures around ω/ω p ≈ 1.36 due to destructive interference of chirped laser pulses (inset figure 2) similar to Hamazaki et al [15]. Here, we neglected the effect of collisions in the current scheme.…”
Section: Discussionsupporting
confidence: 70%
“…One of which is the application of external magnetic field and suitable frequency chirp. Hamazaki et al [15] have investigated the influence of frequency chirp on THz pulse spectra generated due to optical rectification. They observed that to ensure the smooth and single-peaked THz spectra, pre-compensation for the dispersion of GaP is required.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the application of frequency chirp extends the laser-plasma interaction time and thus facilitates the resonance condition for longer duration, which can be useful in the broadband THz radiation generation. Recently, Hamazaki et al [19] have experimentally investigated the impact of the frequency chirp of the laser pump pulse in broadband THz pulse generation by optical rectification in gallium phosphate by measuring the time domain spectroscopy signals. They also reported the significance of accurate control over the frequency chirp of the laser pulse for producing the broadband THz pulses by optical rectification.…”
Section: Introductionmentioning
confidence: 99%
“…Later in 2013, 300 µW THz average power has been obtained with frequency content up to 2 THz using an Yb-doped fibre amplifier delivering 21 W of average power in 52-fs pulses at a repetition rate of 42 MHz [23]. Broad spectra with frequency content up 5 THz have been achieved both from a 3-W, 120-fs, 100-MHz Yb-doped fibre laser amplifier [24] and a 5-W, 20-fs, 78-MHz Yb-doped fibre laser amplifier [25].…”
Section: Introductionmentioning
confidence: 99%